Explaining Differences in Pandemic Inflation across Countries - Steven B. Kamin; John Kearns; Michael R. Strain (American Enterprise Institute (AEI), 2022)
Consumer price inflation in the United States registered 8.2 percent in April 2022, as measured by the consumer price index (CPI). Core CPI inflation, which excludes the costs of energy and food, printed at 6.1 percent. These are the highest rates since the early 1980s, and have understandably been the focus of concern among policymakers, businesses, and households. In this paper, we assess the relative importance of a multitude of possible factors in explaining the variation in inflation across advanced economies. After estimating 32 bivariate cross-country regressions, we find that the variable that was most robustly correlated with core inflation across advanced economies is the economies' pre-pandemic rate of core inflation. Our preferred model is parsimonious, and predicts US 12-month core inflation of 6.6 percent, close to its actual March value of 6.4 percent. Of that prediction, 3.4 percentage points represents the contribution of pre-pandemic inflation, and 2.6 percentage points stems from the rise in US job openings over the past couple of years, which has been driven in part by fiscal stimulus and accommodative monetary policy. Further research into the channels through which monetary and fiscal stimulus pass through to consumer demand and thus inflation is needed.
Keywords: 330